The ontological characteristics and construction mechanism of low-carbon art in Chinese kung fu films - De Costa, Feroz; Kasimon, Diyana Nawar; Guangsheng, Meng (Pegem Akademi Yayincilik, 2024)
The essence of beauty resides in the liberation of emotions. In comparison to natural objects, artistic objects have a greater propensity to evoke intense and unrestrained emotions in aesthetic subjects. Researchers have categorized these emotions into three types based on their quality and quantity: enlightening free emotion, sensory free emotion, and immersive free emotion. Low-carbon art refers to an artistic text that incorporates objective truth as its defining characteristic in textual composition, while also incorporating intuitive truth, surrealistic truth, or subjective truth as its fundamental condition. Through interaction with aesthetic subjects, low-carbon art stimulates enlightening free emotion and promotes both physical and mental well-being for the individuals involved. Objective truth serves as the necessary and sufficient condition for creating a low-carbon artistic text. There are two primary approaches to achieving objective reality within a low-carbon art text: one is grounded in intuitive reality or surrealistic reality; the second is rooted in subjective truth.